The oviduct of transgenic birds - a source of therapeutic proteins? - Bednarczyk, Marek; Łakota, Paweł; Wawrzyńska, Magdalena (Committee on Biotechnology PAS, 2006)
The use of transgenic mammals for the production of therapeutic proteins was developed over two decades ago, and a number of proteins have been produced in the milk of animals. Therapeutic proteins produced in eggs of transgenic hens have significant advantages over transgenic mammalian systems, including: regular high eggs production, large number of progeny, short generation times, sterile contents of the eggs produced by specific pathogen free chickens and, well characterization of the regulatory sequences of white protein genes similar to human glycosylation of chicken IgGs, etc. In this overview, recent progress in the development of chicken bioreaktors was presented.
Keywords: biotechnology